Pengembangan Strategi Pemasaran Hasil Pertanian Jagung - Mafaza Auliya Farda; Naida Maharani Khomsah; Siti Syara; Khoirina Ayu Wardhani; Maulida Alexandria Dewi; Muhammad Rizki Raihan; Sherley Aurora Puspitasari; Hanifah Nurul Syifa; Suwahono Suwahono (Lembaga Pengembangan Kinerja Dosen, 2024)
Developing a marketing strategy for corn agricultural products is an important step to increase the competitiveness and income of corn farmers in Indonesia. Corn as one of the main agricultural commodities has great potential to meet food and industrial needs. This discussion aims to analyze the current conditions of the corn market, identify the challenges faced by farmers, and formulate effective marketing strategies. The results of the discussion show that factors such as product quality, price and market accessibility greatly influence the success of corn marketing. Apart from that, the use of information technology and digital marketing has also been proven to increase market reach and distribution efficiency. Based on these findings, recommended marketing strategies include strengthening distribution networks, improving product quality through training for farmers, and using digital platforms for marketing. By implementing this strategy, it is hoped that corn farmers can increase their income and contribute to national food security